Učinki vadbe z različnimi fizioterapevtskimi postopki, vključno z vadbo hoje na sistemu Lokomat, pri bolnikih z multiplo sklerozo - Krizmanič, Tatjana (Rehabilitacija (Ljubljana), 2015)
Introduction: One of the main goals of physiotherapy in patients with multiple sclerosis is improving functional walking. The article addresses the effect of conventional physiotherapy and robotic-assisted gait training (using the Lokomat system) on gait function in patients with multiple sclerosis. Methods: Twenty patients were included, 11 men and 9 women. Their mean age was 47 years (range 34-69 years). Nine outpatients received Lokomat-assisted gait training; eleven inpatients received conventional physiotherapy including Lokomat-assisted gait training. The patients were assessed before and after the treatment program using the timed up-and-go test, the 10-meter walk test, and the 6-minute walk test. Descriptive statistics was calculated for all three tests. The baseline measures were compared with those after the treatment program. Absolute and relative improvement was compared between outpatients and inpatients. Exact nonparametric statistical tests were used. Results: A statistically significant improvement after the treatment program was observed in the whole sample regarding all the three tests (timed up-and-go: p=0.001, walking speed in the 10m walk test: p=0.012, distance walked in 6 minutes: p=0.019). Inpatients achieved higher average and median absolute and relative improvement on all the three walking tests. The difference between the two groups was statistically significant at the 5% alpha-level only regarding relative improvement in the 6-minute walk test (p=0.046), and came close to that regarding absolute improvement in the 10 m walk test (p=0.080). Conclusions: A combination of conventional physiotherapy and robotic- assisted gait training is recommended in patients with multiple sclerosis. We would have probably proven a statistically significantly larger improvement in the inpatient group regarding all the three walking tests had the number of patients been larger and had the two groups been more comparable in terms of disease stage.
Keywords: gait training; Lokomat; multipla skleroza; Multiple Sclerosis; neurophysiotherapy; nevrofizioterapija; vadba hoje